Finding Aid for the Harold F. Broderick Collection MS.2612 - Broderick, Harold F. (The University of Tennessee Libraries, Knoxville, 1943)
The Harold F. Broderick Collection, 1943, consists primarily of photographs of Attu Island during World War II. Also included is the Blue Star Flag. MS.2612